Identifikasi Penyebab Kerusakan Valve Pada Mud Pump Type Triplex Pump Menggunakan Metode Fault Tree Analysis Di PT. X - Ambri Ambri; Yohanes Yohanes; Yuhelson Yuhelson (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Failure that occurs in mud pump one of which caused by the mud pump valve while the valve failure caused to three (3) components namely the valve complete, valve seat and valve spring. Such failure would cause mud pump unit can not be operated so as to interfere with the smooth operation of drilling. The research was focused on identifying the critical components of the valve and evaluate the cause of the valve failure with fault tree analysis method (FTA). Data that obtained from the company processed using calculations pareto chart and FTA method. Critical component is a valve 3 i.e valve complete. Valve failure caused corrosion, wear and failure rubber valve.Keywords: failure, valve, FTA